2015
DOI: 10.1021/jp5126415
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Nonuniform Sampling NMR

Abstract: Many information rich multi-dimensional experiments in nuclear magnetic resonance spectroscopy can benefit from a signal-to-noise ratio (SNR) enhancement up to about two-fold if a decaying signal in an indirect dimension is sampled with nonconsecutive increments, termed non-uniform sampling (NUS). This work provides formal theoretical results and applications to resolve major questions on the scope of the NUS enhancement. First, we introduce the NUS Sensitivity Theorem, that any decreasing sampling density app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 38 publications
3
104
0
Order By: Relevance
“…al. (Palmer MR et al 2015) turns out to be very close to the traditionally measured SNR (SN rms R) of a reconstructed NUS simulated time-equivalent practical implementation (see below). This is not to state that the iSNR and SN rms R are of the same nature as the rationale behind the two concepts is entirely different.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…al. (Palmer MR et al 2015) turns out to be very close to the traditionally measured SNR (SN rms R) of a reconstructed NUS simulated time-equivalent practical implementation (see below). This is not to state that the iSNR and SN rms R are of the same nature as the rationale behind the two concepts is entirely different.…”
Section: Introductionsupporting
confidence: 77%
“…The non-Gaussian character can be described by calculating the kurtosis value, the fourth standardized statistical moment. In (Palmer MR et al 2015), the group extend the work of (Rovnyak et al 2004), now to include NUS sampling profiles. Both studies calculate iSNR formulae in the time-domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is no general consensus for how far an indirect dimension should be sampled (Hyberts et al 2013) though the signal-to-noise ratio (S/N) is maximized when the indirect dimension is sampled to 1.26*T 2 (Rovnyak et al 2004) and resolution is maximized when the indirect dimension is sampled to 3.14*T 2 . However, recent work has shown that weighted NUS can lead to simultaneous improvements in S/N and resolution beyond 1.26*T 2 (Palmer et al 2015). Sampling to maximize the resolution or sometimes even the S/N can lead to prohibitively long experiment times for serially collected data.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than discrete Fourier transform, NUS data sets are processed using reconstruction algorithms (68). Non-uniform sampling using random schedules weighted by a decaying function results in bona fide time domain sensitivity enhancements by reducing the number of points acquired, thereby allowing for more transients to be acquired in a given time frame (6972). NUS can also be used to obtain resolution enhancement by acquiring out to a longer acquisition time without increasing the number of points.…”
Section: Methods For the Study Of Biomolecules At Ultrahigh Magnetic mentioning
confidence: 99%